Talking in clichés the use of stock phrases in discourse and communication - Bullo, Stella 1975-; Bousfield, Derek (Cambridge, United Kingdom Cambridge University Press, 2023)
"Fusing cutting-edge approaches of systemic-functional linguistics and discourse approaches with Interactional and Applied Pragmatics, this book explores the nature and role of clichés, reimagining this often-disparaged form of language as a means to efficient, effective communication and interaction"-- Provided by publisher.
1. On clichés -- 2. Clichés in discourse -- 3. Clichés as argumentative strategies -- 4. Clichés as social cognition -- 5. Clichés as politeness strategies in evaluation -- 6. Clichés as identity markers -- 7. Concluding remarks.
Includes bibliographical references and index.
Keywords: Clichés; Discourse analysis